Human Mesenchymal Stromal Cells: Identifying Assays to Predict Potency for Therapeutic Selection. (29th January 2013) - Deskins, Desirae L.; Bastakoty, Dikshya; Saraswati, Sarika; Shinar, Andrew; Holt, Ginger E.; Young, Pampee P.
Abstract : The goal of this study was to identify feasible and reproducible in vitro assays to predict mesenchymal stromal cell (MSC) potency. MSC lines were generated from normal human bone marrow samples and characterized by their growth, proliferation, and viability as determined by cell count, bromodeoxyuridine incorporation, and cellular ATP levels, respectively. It was found that high performance in a combination of in vitro tests accurately predicted which lines functioned well in vivo, suggesting that reliable and reproducible in vitro assays may be used to measure the functional potential of MSCs for therapeutic use. Abstract : Multipotent mesenchymal stromal cells (MSCs) have the potential to repair and regenerate damaged tissues, making them attractive candidates for cell‐based therapies. To maximize efficacy of MSCs, prediction of their therapeutic abilities must be made so that only the best cells will be used. Our goal was to identify feasible and reproducible in vitro assays to predict MSC potency. We generated cell lines from 10 normal human bone marrow samples and used the International Society for Cellular Therapy's minimal criteria to define them as MSCs: plastic adherence, appropriate surface marker expression, and trilineage differentiation. Each MSC line was further characterized by its growth, proliferation, and viability as determined by cell count, bromodeoxyuridine incorporation, and cellular ATP levels, respectively. To determine whether these tests reliably predict the therapeutic aptitude of the MSCs, several lines were implanted in vivo to examine their capacity to engraft and form granulation tissue in a well‐established murine wound model using polyvinyl alcohol sponges. Long‐term engraftment of MSCs in the sponges was quantified through the presence of the human‐specific Alu gene in sponge sections. Sections were also stained for proliferating cells, vascularity, and granulation tissue formation to determine successful engraftment and repair. We found that high performance in a combination of the in vitro tests accurately predicted which lines functioned well in vivo. These findings suggest that reliable and reproducible in vitro assays may be used to measure the functional potential of MSCs for therapeutic use.